Full Range Analysis and Application of Frozen Leg Operation for 3-Phase DAB Converters With Open-Circuit Failure - Cun Wang; Jennifer Bauman (IEEE Access)
The three-phase dual-active-bridge (3p-DAB) converter possesses inherent fault-tolerant capability to address open-circuit failures (OCFs). The frozen leg method tackles OCFs without additional hardware by disabling the two switches in the faulty leg, allowing the 3p-DAB to transfer reduced power, generally by maintaining the original phase shift angle. However, prior literature on the frozen leg method focused only on operation with phase shift angles from 0 to $π/3$ . The power transfer characteristics beyond this range, specifically from $π/3$ to $π/2$ , have not been explored in the literature. To address this gap, this paper derives novel equations to describe the transferred power of a 3p-DAB operating with frozen leg control over the phase shift range of $π/3$ to $π/2$ . These equations show for the first time that the theoretical maximum power transfer during frozen leg operation is 75.6% of the normal operation maximum power transfer. Further, based on the derived curves, this paper proposes a method to increase power transfer of the frozen leg method by dynamically adjusting the phase shift angle, which would not be possible without the full power transfer curve from 0 to $π/2$ . The soft-switching analysis for the proposed method is also presented. The theoretical analysis and proposed method are validated through extensive experimental testing.